O ensino do léxico de língua portuguesa na educação de jovens e adultos (EJA) - Freitas, Juliane Pereira Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Lexical competence is an aspect that has been studied in various fields of education, but is not observed special attention for the Youth and Adult Education (EJA). Whereas the development of lexical competence contributes to the development of communicative competence of the student in adult education, teaching lexicon in this modality is very importance, because it enables an effective integration into the world of writing and they also extend their social participation in the exercise of citizenship. So the more encouraged and exploited for the teaching of vocabulary in classroom, the more this student will have the ability and domain when dealing with the most varied situations for using the language, whether in written or spoken language. This dissertation aims to investigate the applicants strategies in textbooks (LD) Tempo de Aprender and EJA - Mundo do Trabalho and the strategies used by portuguese teachers in classrooms of EJA, in order to enrich the lexical vocabulary of the student. Therefore, we used as research tools, analysis from exercices of two teaching materials (Tempo de Aprender and EJA - Mundo do Trabalho), questionnaires with students and teachers, interviews with teachers and unstructured registration of classes observations and field observation. The field research was conducted in two schools - in a municipal school Icém (SP) and in a state school of Fronteira (MG) - in order to compare the methodology used by teachers in relation to the lexicon teaching these schools environments from different states, with different pubic policies, but with location next. From the analysis, we observed that that both authors and teachers favored working with simple words at the expense of complex words, regardless their lexical richness and its importance in teaching. In addition, the dictionary is unexplored by the teachers and LD, although the teachers claiming to know the importance of dictionary for student learning ...

A competência lexical é um aspecto que vem sendo estudado em vários âmbitos da educação, porém não se observa atenção especial em relação à Educação de Jovens e Adultos (EJA). Considerando que o desenvolvimento da competência lexical contribui para o desenvolvimento da competência comunicativa do estudante na EJA, o ensino do léxico nessa modalidade é de suma importância, pois possibilita sua (re)inserção efetiva no mundo da escrita e amplia sua participação social no exercício da cidadania. Dessa maneira, quanto mais estimulado e explorado for o ensino do léxico em sala de aula, mais esse educando terá a capacidade de lidar com eficiência nas mais variadas situações de usos da língua, seja no eixo oral ou no escrito. Esta dissertação objetiva investigar as estratégias recorrentes nos livros didáticos (LD) Tempo de Aprender e EJA - Mundo do Trabalho e as utilizadas pelos professores de Língua Portuguesa em salas de ensino fundamental II da EJA, com a finalidade de enriquecer o acervo lexical do educando. Para tanto, utiliza-se como instrumentos de pesquisa, análises de exercícios dos materiais didáticos supracitados, questionários com discentes e docentes, entrevistas com professores e observações de aulas registradas de forma não estruturada. A pesquisa em campo foi realizada em duas escolas - uma escola municipal de Icém (SP) e outra estadual de Fronteira (MG) - a fim de comparar a metodologia utilizada pelas professoras em relação ao ensino do léxico nesses ambientes escolares de estados diferentes, com políticas púbicas diferentes, porém com localização próxima. A partir da análise, foi possível verificar que tanto os autores dos LD analisados quanto as professoras participantes privilegiam o trabalho com lexias simples em detrimento das complexas, desconsiderando sua importância no ensino. Além disso, o dicionário é pouco explorado pelas professoras e nos LD, apesar de as...
Keywords: Linguistica aplicada; Língua portuguesa - Lexicologia; Língua portuguesa - Português escrito; Educação de adultos - Livros didáticos; Applied linguistics